Assessing the variability of 23Na MRI in skeletal muscle tissue: Reproducibility and repeatability of tissue sodium concentration measurements in the lower leg at 3 T. (3rd March 2020) - Gerhalter, Teresa; Gast, Lena V.; Marty, Benjamin; Uder, Michael; Carlier, Pierre G.; Nagel, Armin M.
Abstract : The goal of this study was to evaluate the reproducibility and repeatability of tissue sodium concentration (TSC) measurements using 23 Na MRI in skeletal muscle tissue. 23 Na MRI was performed at 3 T on the right lower leg of eight healthy volunteers (aged 28 ± 4 years). The examinations were repeated at the same site after ~ 22 weeks to assess the variability over a medium‐term period. Additionally, they were scanned at a second site shortly before or shortly after the first visit (within 3 weeks) to evaluate the inter‐site reproducibility. Moreover, we analysed the effect of B0 correction on the variability. Coefficients of variations (CVs) from mean TSC values as well as Bland–Altman plots were used to assess intra‐site repeatability and inter‐site reproducibility. In phantom measurements, the B0 correction improved the quantitative accuracy. We observed differences of up to 4.9 mmol/L between the first and second visit and a difference of up to 3.7 mmol/L between the two different sites. The CV for the medium‐term repeatability was 15% and the reproducibility CV was 9%. The Bland–Altman plots indicated high agreement between the visits in all muscle regions. The systematic bias of −0.68 mmol/L between site X and Y ( P = 0.03) was slightly reduced to −0.64 mmol/L after B0 correction ( P = 0.04). This work shows that TSC measurements in healthy skeletal muscle tissue can be performed with good repeatability and reproducibility, which is of importance for future longitudinal or multicentre studies. Abstract : 23 Na MRI represents an emerging method to characterise the (patho‐) physiological changes in skeletal muscle. Here, we assessed the inter‐ and intra‐site variability of tissue sodium concentration (TSC) measurements in skeletal muscle tissue of healthy subjects. The Bland–Altman plots and coefficients of variation indicated high agreement between the visits in all muscle regions. Our work shows that TSC measurements of skeletal muscle can be performed with good repeatability and reproducibility, which is of importance for longitudinal or multicentre studies.